A technically sustainable E‐bus based transit system for Indian cities - Suman Majumder; Krishnarti De; Praveen Kumar (IET Electrical Systems in Transportation)
Abstract The exponential increase in the number of internal combustion engine vehicles due to rapid urbanization results in traffic congestions and air pollution. A paradigm shift towards public transportation system using an electric vehicle can be a possible solution for this issue. However, for such a system to be effective, it is necessary to study its impact on the electricity grid, and also to size the subsystems appropriately. Hence, in this work, an E‐bus based transportation system with the preliminary sizing of subsystems is proposed. In order to ensure that the proposed transportation system does not overburden the grid, distributed solar energy generation is used as an additional source. The energy required for transportation system is stored in a high capacity storage device from grid and solar. The high capacity storage device is further used to stabilize the grid through peak shaving and valley filling. The systematic energy flow between subsystems is ensured by using a fuzzy logic control algorithm. The feasibility of the proposed system is analysed for Guwahati city, Assam, India, for its driving pattern and different seasonal variations of grid demand and solar irradiation. The results of the analysis show that with proper sizing and energy management, a viable E‐bus based transportation system can be obtained for Indian cities.